Deficiency in Mucosa-associated Lymphoid Tissue Lymphoma Translocation 1: A Novel Cause of IPEX-Like Syndrome. Issue 3 (March 2017) - Charbit-Henrion, Fabienne; Jeverica, Anja K.; Bègue, Bernadette; Markelj, Gasper; Parlato, Marianna; Avčin, Simona Lucija; Callebaut, Isabelle; Bras, Marc; Parisot, Mélanie; Jazbec, Janez; Homan, Matjaz; Ihan, Alojz; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objective: Early-onset inflammatory bowel diseases can result from a wide spectrum of rare mendelian disorders. Early molecular diagnosis is crucial in defining treatment and in improving life expectancy. Herein we aimed at defining the mechanism of an immunodeficiency-polyendrocrinopathy and enteropathy-X-linked (IPEX)–like disease combined with a severe immunodeficiency in 2 siblings born from distantly related parents. Methods: Whole exome sequencing was performed on blood-extracted genomic DNA from the 2 affected children and their parents on the genomic platform of Institut IMAGINE. Candidate gene mutation was identified using the in-house software PolyWeb and confirmed by Sanger sequencing. Protein expression was determined by western blot. Flow cytometry was used to assess consequences of the mutation on lymphocyte phenotype and nuclear factor-kappa B (NF-κB) activation at diagnosis and after treatment by hematopoietic stem cell transplantation. Results: We identified a homozygous missense mutation in mucosa-associated lymphoid tissue lymphoma translocation 1 gene ( MALT1 ), which precluded protein expression. In keeping with the known function of MALT1, NF-κB–dependent lymphocyte activation was severely impaired. Moreover, there was a drastic reduction in Forkhead box P3 (FOXP3) regulatory T cells accounting for the IPEX-like phenotype. Following identification of the mutation, both children received hematopoietic stem cell transplantation, which permitted full clinical recovery. Immunological workup at 6 and 12 months after transplantation showed normal NF-κB activation and correction of regulatory T cells frequency. Conclusions: Along with FOXP3, interleukin 2 receptor alpha chain (IL2RA), and cytotoxic T-lymphocyte protein 4 precursor (CTLA-4) mutations, MALT1 deficiency should now be considered as a possible cause of IPEX-like syndrome associated with immunodeficiency that can be cured by hematopoietic stem cell transplantation.